G42(P) Epidemiology and outcome of status epilepticus in children with new ILAE definition. (25th October 2020) - Mitchell, C; Dickson, L; Ramsay, A; Leonard, P; Brand, C; McLellan, A; Shetty, J
Abstract : Background: Status Epilepticus (SE) in children carries significant risk of morbidity and mortality. Previous work has predominantly focused on SE ≥30 min but a new ILAE definition has been produced following evidence that seizures ≥5 min are associated with negative outcomes. This study aims to evaluate the epidemiology and outcome of SE since the introduction of buccal midazolam, change in ILAE definition and increased involvement of specialist epilepsy nurses. Methods: Multiple datasets were combined to identify all children presenting to accident and emergency (A+E) between 2011–2017 in the region. Data was collated from electronic health records; including patient demographics, clinical characteristics, acute seizure management and outcomes. This data can be used to study long-term outcomes, including educational outcome, through national data linkage systems. Results: There were 665 children admitted with SE who had 1228 seizure episodes during the study period. SE accounted for 0.38% (95%CI 0.34–0.42%) of annual A+E admissions. Yearly prevalence, calculated using mid-year-population estimate, was 0.8 per 1000 children. 57.3% of patients were male (95% CI 53.5–61.1%) and median age was 3.65 years (IQR=6.33, Min=0.0, Max=20.97). There is a small deprivation effect (p=0.0006) which is most prominent at ages 2–3. The median number of PS for each child was 1, however, 34.1% of children had recurrent SE and 5.6% had ≥5 SE. Median seizure duration was 10 min. 30.3% of seizures lasted between 5–29 min. Recurrent seizures and longer duration both increased odds of negative outcome. Buccal midazolam was used in the management of 28.9% of seizures and had no effect on the need for ventilatory support. The majority of seizures (69.8%) required admission to hospital and only 4.0% resulted in adverse outcome. Of 1228, there were 2 deaths (0.2%). Compared to symptomatic seizures, unprovoked seizures had a longer average duration, higher likelihood of negative outcomes and there was a higher proportion of those with other neurological diagnosis. Conclusions: Adverse outcomes have decreased and the use of buccal midazolam is promising. Identifying high-risk groups provides opportunity for early intervention. This data forms the basis for extensive evaluation of acute seizure management and monitoring long-term outcomes.